Vedāntakalpataruparimalaḥ : Bhagavadamalānandayatīndraviracitavedāntakalpataruvyākhyārūpaḥ - Appayya Dīkṣita (Bhāratīya Vidyā Prakāśana, 1992)
Supercommentary on the Vedāntakalpataru of Amalānanda, 13th cent., commentary on the Bhāmatī of Vācaspatimiśra, fl. 976-1000; Advaita viewpoint.